Result Component of Individual Education - Dehqanova Muborakxon G’iyeziddin qizi (Scientific Trends, 2024)
This article provides information about effectiveness, which is one of the effective components of individual education.
Keywords: Individual education, approach, didactics, complexity, teacher-student.